Pengaruh Brand Awereness, Brand Image Dan Brand Trust Terhadap Keputusan Pembelian Produk Laptop Lenovo - Ikrima Nizzul Mefiandini; Eka Farida; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the influence of brand awareness, brand image, and brand trust on Lenovo laptop purchasing decisions made by Lenovo laptop users in the city of Malang. The type of research used is quantitative. The sample for this study was taken using the accidental sampling technique or sampling that was carried out by chance, that is, anyone who met the researcher by chance could be used as a sample using the Maholtra formula, namely the number of indicators × 5 so that the total sample was 80 respondents. The data analysis method used in this study is multiple linear regression analysis. Using (F test) for simultaneous hypothesis testing and (t test) for partial testing. The results of this study indicate that simultaneously brand awareness, brand image, and brand trust have a significant effect on purchasing decisions for Lenovo laptops. Meanwhile, partially brand awareness has no significant effect on purchasing decisions, brand image partially has a significant effect on purchasing decisions, and brand trust has no significant effect on purchasing decisions for Lenovo laptops. Keywords: Brand Awereness, Brand Image, Brand Trust, and Purchase Decision.